Bio-mimicry and Urban Design A case study of Sheikh Mohammed bin Zayed City - TIMRAZ, AHMAD F.M. (2018)
I would like to thank and appreciate the hard work and the best advice from my advisor, Dr. Hanan Taleb, and her continuous support. I am also very grateful to my family for their continued support and their prayer to me to have a successful journey in BUID and in the rest of my life. Finally, many thanks to all professors and academic staff who were there to develop my learning skills and knowledge in order to increase my efficient working experience in both academic and working fields.